Autonomous optimisation of a nanoparticle catalysed reduction reaction in continuous flow. Issue 40 (19th April 2021) - Hall, Brendan L.; Taylor, Connor J.; Labes, Ricardo; Massey, Alexander F.; Menzel, Robert; Bourne, Richard A.; Chamberlain, Thomas W.
Abstract : An automated continuous flow reactor system for the optimisation of nanoparticle catalysed reactions, demonstrated through the optimisation of a gold nanoparticle catalysed nitrophenol reduction reaction. Abstract : An automated continuous flow reactor system equipped with inline analysis, was developed and applied in the self-optimisation of a nanoparticle catalysed reaction. The system was used to optimise the experimental conditions of a gold nanoparticle catalysed 4-nitrophenol reduction reaction, towards maximum conversion in under 2.5 hours. The data obtained from this optimisation was then used to generate a kinetic model, allowing us to predict the outcome of the reaction under different conditions. By combining continuous flow nanoparticle synthesis with this approach, the development timeline for these emerging catalysts could be significantly accelerated.